Alternative fiscal visibility estimates for some OECD countries with three levels of territorial government levels - Miguel Roig-Alonso (European Regional Science Association (ERSA), 2002)
The size and pattern of any public budget depend, among other factors, on the visibility of both the burdens and benefits of public revenue and expenditure. Furthermore, such visibility is a necessary - not a sufficient - condition for an efficient allocation of resources between the private and public sector of an economy. Although the importance of this visibility has been well known by academicians and practitioners for a long time, attempts to quantify it by taking the internal structure of every type of revenue or expenditure and its relative financial weight in a fiscal system into consideration are recent, and indicators used till now rest on several structural parameters, each of them conventionally ranging from 0 to 1, which are combined in a multiplicative way. For this reason, a 0 estimate will always result as one of such factors is, at least, also 0. Starting from the same parameters, factors, and initial values, an alternative and probably more fruitful way to measure visibility of burdens and benefits of a public budget can consist of combining them in an additive instead of multiplicative way. Then a null parametric value will not result in a 0 estimate, and calculations can show higher final values which could be much more sensitive to the initial values of other parameters and factors. The aim of this contribution, based on a recent research, is to present and compare new additive indicators applied to local, intermediate, and central territorial government levels in Austria, Canada, Germany, Spain, Switzerland, and USA by using data and qualitative information provided by the International Monetary Fund. Comparisons, conclusions, and comments are offered for general criticism, discussion, and development.
Keywords: 330